Functionally reproductive diploid and haploid males in an inbreeding hymenopteran with complementary sex determination - Cowan, David P. (National Academy of Sciences, 2004)
It has become a matter of orthodoxy that among wasps, ants, bees, and other insects in the order Hymenoptera, only uniparental haploid males that arise from unfertilized eggs are capable of reproduction. This idea is of interest because the best understood and perhaps most widespread sex determination system among these insects [known as single locus complementary sex determination (sl-CSD)] does not depend on ploidy alone and, paradoxically, consistently results in small numbers of diploid biparental males. To date, the reproductive potential of diploid males has been studied in 13 of the perhaps 200,000 hymenopterans world-wide; in each of these instances, the diploid males are genetic dead ends because they are inviable or sterile. The data from these species have resulted in a general conclusion that has been invoked for virtually all species with sl-CSD and has become the basis for assumptions regarding conservation biology, sex ratio analysis, and the evolution of social behavior. Here, we report that in the solitary vespid wasp Euodynerus foraminatus, both diploid and haploid males are fertile, which documents normal fertility in diploid males of a hymenopteran with sl-CSD. This wasp has high levels of inbreeding because of frequent brother–sister mating in nature; therefore, diploid males are more frequently produced and thus more likely exposed to selection favoring their fertility. Because inbreeding and diploid male production may be important features of the population biology of many hymenopterans, we sound a cautionary note regarding ideas about the evolutionary ecology of these insects.